2000
DOI: 10.1046/j.1523-1755.2000.00268.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct structural forms of type I collagen modulate cell cycle regulatory proteins in mesangial cells

Abstract: The growth-inhibitory effect of polymerized type I collagen is characterized by rapid changes of expression and/or activation of MAPK and G1-phase regulators and could result from the lack of alpha1beta1 integrin signaling in MCs on polymerized type I collagen. Conceivably, deposition of polymerized type I collagen might reflect a reparative response to control MC replication in glomerular inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Many reports suggest that integrin signaling induces proliferation of cells, including mesangial cells, mammary epithelial cell, and mesenchymal cells, in the presence of ECM (Schöcklmann et al 2000, Li et al 2005, Fernandes et al 2006. Integrins comprise an a-subunit and a b-subunit that form a heterodimer.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports suggest that integrin signaling induces proliferation of cells, including mesangial cells, mammary epithelial cell, and mesenchymal cells, in the presence of ECM (Schöcklmann et al 2000, Li et al 2005, Fernandes et al 2006. Integrins comprise an a-subunit and a b-subunit that form a heterodimer.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this treatment restored the changes in the cellular content and surface expression of P-selectin, VCAM-1 and MCP-1 mRNA expression detected in HuVEC seeded on this interstitial collagen. This experimental approach is normally used in this type of studies [35,36]. Pepsin removes the aminotelopeptide sequences of collagen type I, disrupts the intermolecular crosslinking between telopeptides and the triple helix structure.…”
Section: Discussionmentioning
confidence: 99%
“…When polymerized into fibrils, as it is mostly found in vivo, type I collagen inhibits growth of a number of cell types including smooth muscle cells (Koyama et al, 1996), melanoma cells (Henriet et al, 2000), glomerular epithelial cells (Schocklmann et al, 2000), and hepatocytes De Smet et al, 2001), whereas adhesion to monomeric collagen stimulates cell cycle progression under similar culture conditions. Unlike loss of adhesion, however, which blocks cell cycle progression and also induces apoptosis, adhesion to collagen gels promotes survival and increased differentiated function (Ben-Ze'ev et al, 1988;Gomez-Lechon et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Decreased cyclin D1 expression Schocklmann et al, 2000), and/or increased expression of cell cycle inhibitor proteins such as p21 or p27 KIP (Koyama et al, 1996;Henriet et al, 2000) have been demonstrated in various cell types in response to adhesion to fibrillar collagen. The mechanisms by which adhesion to fibrillar collagen modulates the signaling pathways that determine the expression levels of cell cycle regulatory proteins, however, are not well defined.…”
Section: Introductionmentioning
confidence: 99%